Planejamento da logística reversa do óleo residual de fritura para uma destinação ambientalmente correta - Gonçalves, Max Filipe Silva (2016)
Increased waste generation affects the daily lives of millions of people, but the practice of proper disposal of this waste is recent in Brazil, driven by the National Policy on Solid Waste (PNRS) enacted in 2010. Among the waste, used cooking oil from households, commerce and industry, is a potentially polluting waste when disposed of improperly. Therefore it is necessary to focus on other destinations, such as to home-made soap, paint, biodiesel as others. However, a difficulty in the utilization of this waste is to have a sufficient volume and is provided at low cost so as to enable these processes. In this sense, the objective of this work is to propose a reverse logistics network for this waste by means of a mathematical model for defining return centers minimizing the cost of installation and operation of the network. The model was validated by application in Linhares, north of Espírito Santo. They selected six scenarios based on real data that were run on IBM Solver CPLEX 12.6. With the results obtained, it was possible to assess on alternatives to reverse logistics network. The discussion permeates the economic, legal and environmental drivers. It was possible to see the impact on the total costs of the network with the allocation of facilities in different places, depending on the collected waste volume, and the residue sending flow of the neighborhoods for pre- treatment centers and those for local recycling. It was found that transport costs are more striking than the installation costs. The optimization of reverse logistics network of waste contributes to its implementation and reuse of a harmful waste to the environment, but it can be used as raw material in another productive process, provided it is collected and treated properly.